PENGEMBANGAN LEMBAR KERJA SISWA PRAKTIKUM BERBASIS KONSTRUKTIVISME PADA MATERI MOLLUSCA - KUSUMA RAHMAWATI, EVA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The study kingdom of animal can be tought with direct observation. One of the approaches that can used is constructivism. The purpose of this were to develop worksheet experiment by constructivism Phylum Mollusca in grade X Senior High School to describe theoretical feasibility of worksheet based on the expert validation and describe the empirical feasibility of the worksheet based on student’s activity and student’s responses. This research was development research which used 4D models, which cinsisted of four steps, namely define, design, develop, and disseminate. However, the step of dissemintate was not be done.. The results showed that the theoretical fesibility got average scores 3,54 (very good). The based of student activity showed that worksheet got average scores 94.66% (very good). The result of student responses showed got positive responses from students namely 89.4% (very good). Key words: worksheet, constructivism, Phylum Mollusca, 4D models, Biology Class X Senior High School.